PHYSICAL EDUCATION AND MORAL DEVELOPMENT IN EARLY CHILDHOOD EDUCATION (Fiep Bulletin - online, 2014)
The purpose of this article was to discuss and discover the implications of Physical Education and Moral Development in Early Childhood Education , this investigation was characterized by a qualitative study is an exploratory and descriptive, context chosen for the study was comprised of three schools are Luís-MA., two private and one public. The sample universe was composed of nine teachers in total with three teachers from each school, the same was applied a questionnaire with open questions about their conceptions of Integral Development in Early Childhood Education. It was found that the teachers surveyed have knowledge and understand the Integral Development, however, one realizes that there are still few studies related to the development of the child by the Comprehensive Physical Education academics.
Keywords: Moral Development; Early Childhood Education; Physical Education